Contemporary Topics in Graduate Medical Education - Stawicki, Stanislaw P.; Firstenberg, Michael S.; Orlando, James P.; Papadimos, Thomas J. (IntechOpen, 2019)
Graduate medical education (GME) is a continually evolving, highly dynamic area within the complex fabric of the modern health-care environment. Given the rapidly changing regulatory, financial, scientific and technical aspects of GME, many institutions and programs face daily challenges of "keeping up" with the most recent developments within this ever-more-sophisticated operational environment. Organizational excellence is a requirement for the seamless functioning of GME programs, especially when one consider the multiple disciplines and stakeholders involved. The goal of the current book cycle, titled Contemporary Topics in Graduate Medical Education, beginning with this inaugural tome, is to provide GME professionals with a practical and readily applicable set of reference materials. More than 20 distinguished authors from some of the top teaching institutions in the US, touch upon some of the most relevant, contemporary, and at times controversial topics, including provider burnout, gender equality issues, trainee wellness, scholarly activities and requirements, and many other theoretical and practical considerations. We hope that the reader will find this book to be a valuable and high quality resource of a broad range of GME-related topics. It is the Editors' goal to create a multi-tome platform that will become the definitive go-to reference for professionals navigating the complex landscape of modern graduate medical education.